PENGENDALIAN KUALITAS PROSES PRODUKSI SEPATU DENGAN PETA KENDALI P MULTIVARIAT - Yuli Suwarno; Jamila Jamila (Politeknik ATK Yogyakarta, 2015)
Very hard competition in industrial world forces each industry to focus on product quality. Quality control play important role. In other side product quality is not only limited on one quality characteristic but on some characteristics that need special method in controlling. The research applied quality control method of P multivariate control chart in PT Forta La Rese a producer of safety shoe and was done in lasting process. In lasting process section, of 15 defect types, there were only 7 defect types that were consistent and often occur. So, this quality control used the seven defect types consisting of wrinkled, incline lasting, rough assembly, rough smoothing, torn leather, crack, and defect leather. Production process of safety shoe in PT Forta La Rese in lasting process indicated statistically uncontrolled results. It was due to four observations (5, 8, 13, and 21) that were above upper control limit. Based on analysis there were 6 defect types as dominant cause of entire defect proportion above upper control limit consisting of defect leather, wrinkled, torn leather incline lasting, rough assembly and crack. Causes of the defects are low quality of leather material and operator error in leather checking process, assembly and lasting process.